2017
DOI: 10.1016/j.otsr.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Posterior shoulder instability: Prospective non-randomised comparison of operative and non-operative treatment in 51 patients

Abstract: III, case-control study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…14 Arthroscopic posterior capsulolabral repair has demonstrated improvements in clinical outcome scores and return to play of up to 88% for nonthrowing athletes. 2,6,10,11,16,18,26 Similar improvements in clinical outcomes postoperatively and return to play have been found in throwing athletes. 20…”
supporting
confidence: 69%
“…14 Arthroscopic posterior capsulolabral repair has demonstrated improvements in clinical outcome scores and return to play of up to 88% for nonthrowing athletes. 2,6,10,11,16,18,26 Similar improvements in clinical outcomes postoperatively and return to play have been found in throwing athletes. 20…”
supporting
confidence: 69%
“…The clinical treatment depends on a number of anatomical and functional factors that must be evaluated in each patient. The treatment can be either nonoperative or surgical: The nonoperative approach is adopted when the dislocation is stable after a reduction maneuver and when there are no significant bone deficits; after the maneuver, the shoulder is immobilized for a limited period of time [8,9]. On the other hand, surgical treatments are preferred when the trauma has caused joint instability or lesions of bone or soft tissues that require surgical stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of the operative technique depends on the joint defect: anatomical reconstruction of the articular surface is recommended for deficits between 25 and 40%, while prosthetic surgery is usually preferred for injuries that reduce the shoulder mobility by more than 40%. In 2017, the French Society of Arthroscopy [8] compared the clinical outcomes of nonoperative and surgical treatments in a prospective multi-center non-randomized study, and they showed that operative techniques have better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…32,39 When conservative treatment fails, surgery is recommended to grant long-term stability, prevent pain, and enable return to previous activity levels. 10,12,13,26,33,38 Glenoid fractures and bone loss are frequently treated by bone-block procedures, while labral tears are commonly treated by the Bankart procedure. 1,6,9,25,26,28 The choice of surgical technique is critical and requires meticulous analysis of numerous preoperative imaging and clinical findings.…”
mentioning
confidence: 99%
“…45 Posterior shoulder instability, especially in patients with atraumatic lesions, engenders multiple nonspecific symptoms, including pain, subluxation, and functional impairment, which complicate its diagnosis and management. 4,13,38,39,45 Conservative treatment of posterior shoulder instability has low success rates, 12,23,37,38,45 especially in patients with traumatic lesions. 32,39 When conservative treatment fails, surgery is recommended to grant long-term stability, prevent pain, and enable return to previous activity levels.…”
mentioning
confidence: 99%